PCSK9-D374Y mediated LDL-R degradation can be functionally inhibited by EGF-A and truncated EGF-A peptides: An in vitro study. (January 2020) - Valenti, Vincenza; Noto, Davide; Giammanco, Antonina; Fayer, Francesca; Spina, Rossella; Altieri, Grazia I.; Ingrassia, Valeria; Scrimali, Chiara; Barbagallo, Carlo M.; Brucato, Federica; Misiano, Gabriella; Cefalù, Angelo B.; et al.
Abstract: Background and aims: Proprotein convertase subtilisin/kexin type 9 (PCSK9) binds to low density lipoprotein receptor (LDLR) through the LDLR epidermal growth factor-like repeat A (EGF-A) domain and induces receptor internalization and degradation. PCSK9 has emerged as a novel therapeutic target for hypercholesterolemia. Clinical studies with PCSK9 inhibiting antibodies have demonstrated strong LDL-c lowering effects, but other therapeutic approaches using small molecule inhibitors for targeting PCSK9 functions may offer supplementary therapeutic options. The aim of our study was to evaluate the effect of synthetic EGF-A analogs on mutated (D374Y) PCSK9-D374Y mediated LDLR degradation in vitro . Methods: Huh7 human hepatoma cells were transiently transfected to overexpress the gain-of-function D374Y PCSK9 mutation, which has been associated with severe hypercholesterolemia in humans. Results: Transient transfection of cells with PCSK9-D374Y expression vector very effectively enhanced degradation of mature LDLR in Huh7. Treatment with both EGF-A and EGF-A truncated peptides inhibited this effect and showed increased LDLR protein in Huh7 cells transfected with PCSK9-D374Y in a clear concentration dependent manner. Huh7 transfected cells treated with increasing concentration of EGF-A analogs also showed an increase internalization of labeled Dil-LDL. Conclusions: The result of our study shows that EGF-A analogs are able to effectively hamper the enhanced degradation of LDLR in liver cells expressing PCSK9-D374Y. Graphical abstract: Image 1 Highlights: PCSK9 acts by binding to the EGF-A domain of LDLR and promotes its degradation. Gain-of-function D374Y PCSK9 mutation causes severe hypercholesterolemia in humans. PCSK9-D374Y mediated LDLR degradation is inhibited by EGF-A analogs in vitro .